Reduced Oblique Effect in Children with Autism Spectrum Disorders (ASD) - Sysoeva, Olga V.; Davletshina, Maria A.; Orekhova, Elena V.; Galuta, Ilia A.; Stroganova, Tatiana A. (Frontiers in Neuroscience, 2016)
People are very precise in the discrimination of a line orientation relative to the cardinal (verti-cal and horizontal) axes, while their orientation discrimination sensitivity along the oblique ax-es is less refined. This difference in discrimination sensitivity along cardinal and oblique axes is called the “oblique effect”. Given that the oblique effect is a basic feature of visual pro-cessing with an early developmental origin, its investigation in children with Autism Spectrum Disorder (ASD) may shed light on the nature of visual sensory abnormalities frequently report-ed in this population. We examined line orientation sensitivity along oblique and vertical axes in a sample of 26 boys with ASD (IQ > 68) and 38 typically developing (TD) boys aged 7-15 years, as well as in a subsample of carefully IQ-matched ASD and TD participants. Children were asked to detect the direction of tilt of a high-contrast black-and-white grating relative to vertical (90°) or oblique (45°) templates. The oblique effect was reduced in children with ASD as compared to TD participants, irrespective of their IQ. This reduction was due to poor orien-tation sensitivity along vertical axis in ASD children, while their ability to discriminate line orientation along oblique axis was unaffected. We speculate that this deficit in sensitivity to vertical orientation may reflect disrupted mechanisms of early experience-dependent learning that takes place during the critical period for orientation selectivity.